ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN DAN PERSEDIAAN DI UD DONGMART BERBASIS WEB - Kadek Intan Janeta Pratiwi; Ni Made Satvika Iswari; Ni Putu Noviyanti Kusuma (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to address the issues of effectiveness and efficiency in transaction recording and data security at UD DongMart, a household goods trading business. The research method employed is Prototype approach, which is iterative and interactive, allowing users to provide feedback during system development. The stages include requirements analysis, system design using tools such as flowcharts, Data Flow Diagrams (DFD), and Entity-Relationship Diagrams (ERD), and prototype development using HTML, CSS, and Bootstrap. System evaluation was conducted through demo and guerilla testing, yielding positive user responses regarding the usability and design of the system. The findings indicate that the proposed information system successfully enhances transaction recording speed and accuracy, reduces data input errors, and improves data security, meeting the operational needs of UD DongMart and supporting small and medium-sized business growth.